2004
DOI: 10.1177/001857870403900807
|View full text |Cite
|
Sign up to set email alerts
|

Using a Data Warehouse to Monitor Clinical Outcomes Associated with Simvastatin Tablet Splitting

Abstract: A data warehouse was used to monitor therapeutic outcomes for a simvastatin tablet-splitting initiative. The data included prescription and laboratory information for all patients taking simvastatin between October 1, 1998 and February 28, 2003. Among 44,038 patients receiving simvastatin, the low-density lipoprotein (LDL) levels of 194,213 patients were reported. The tablet-splitting initiative was started in April 1999 and 5,683 patients were converted from whole to half tablets. The average LDL for these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Concerning to modified-release tablets, studies using verapamil sustainedrelease tablets did not find statistics differences in bioavailability between split and whole tablets (76,77). A study using theophylline slow-release tablet showed faster absorption and higher plasma levels when volunteers took the halves instead whole (78).…”
Section: Tablet Splitability: Clinical Trialsmentioning
confidence: 99%
“…Concerning to modified-release tablets, studies using verapamil sustainedrelease tablets did not find statistics differences in bioavailability between split and whole tablets (76,77). A study using theophylline slow-release tablet showed faster absorption and higher plasma levels when volunteers took the halves instead whole (78).…”
Section: Tablet Splitability: Clinical Trialsmentioning
confidence: 99%